2003
DOI: 10.1002/app.12101
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion process of amino acids in polymer supports for solid‐phase peptide synthesis as studied by pulsed‐field‐gradient spin‐echo proton nuclear magnetic resonance

Abstract: The diffusion coefficient (D) values of tert- butyloxycarbonyl-glycine, tert-butyloxycarbonyl-l-tryptophan, tert-butyloxycarbonyl-l-phenylalanine (Boc-Phe), and 9-fluorenylmethoxycarbonyl-l-phenylalanine in Merrifield polystyrene (MPS) gels, poly(ethylene glycol)-grafted polystyrene (PEG-PS) gels, and crosslinked ethoxylate acrylate (CLEAR) gels, as used in solid-phase peptide synthesis, were determined by the pulsed-field-gradient spin-echo 1 H-NMR method. From these experimental results, it was found that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Probe molecules used in this work have monodispersity and single component T 2 . In previous works, [21][22][23] we reported that probe molecules in solution have a single diffusion component. Therefore, we think that echo attenuation curvature is not attributed to diffusant polydispersity, trace solvents, T 2weighting, and artifacts, but host inhomogeneity.…”
Section: Resultsmentioning
confidence: 93%
“…Probe molecules used in this work have monodispersity and single component T 2 . In previous works, [21][22][23] we reported that probe molecules in solution have a single diffusion component. Therefore, we think that echo attenuation curvature is not attributed to diffusant polydispersity, trace solvents, T 2weighting, and artifacts, but host inhomogeneity.…”
Section: Resultsmentioning
confidence: 93%
“…[1][2][3][4] Various polymer supports for the solid-phase synthesis of peptides have been studied. 5,6 The recent development of the incorporation of biopolymers with timeresolved fluorescence (TRF) for the imaging and therapy of tumors has become a stimulus for the design and synthesis of novel peptide polymers. [7][8][9] TRF assay systems are widely employed in highthroughput applications.…”
Section: Introductionmentioning
confidence: 99%
“…Two decades of peptide research have yielded a lot of information on the design, synthesis, and characterization of the structures of peptides 1–4. Various polymer supports for the solid‐phase synthesis of peptides have been studied 5, 6. The recent development of the incorporation of biopolymers with time‐resolved fluorescence (TRF) for the imaging and therapy of tumors has become a stimulus for the design and synthesis of novel peptide polymers 7–9.…”
Section: Introductionmentioning
confidence: 99%
“…For small and medium-sized organic reagents, this leads to a reduction of the diffusion coefficient by a factor of typically 3-6 32 (e.g., the diffusion coefficient of BOC-Phe is reduced from D 0 ) 4.8 × 10 -6 cm 2 s -1 in DMF bulk solution to D e ) 0.9 × 10 -6 cm 2 s -1 in DMF-swollen polystyrene beads). 33 More dramatic decreases are observed for higher values of φ, high degrees of cross-linking, larger solute sizes, and strong solute-polymer interactions 32,34 (e.g., the diffusion coefficient of rhodamines is reduced from D 0 ) 2.8 × 10 -6 cm 2 s -1 in water 35 to D e ≈ 10 -7 cm 2 s -1 in solvent-swollen polymer beads 36 and to D e ≈ 5 × 10 -10 cm 2 s -1 in silica sol-gel materials). 23,37,38 For the bead size of d ) 100 µm considered here, the effective rate of the overall reaction shows a pronounced dependence on both k and D S .…”
Section: The Effect Of Diffusion Coefficient and Second-ordermentioning
confidence: 99%